Can citizen scientists provide a reliable geo-hydrological hazard inventory? An analysis of biases, sensitivity and precision for the Rwenzori Mountains, Uganda. (1st April 2022) - Sekajugo, John; Kagoro-Rugunda, Grace; Mutyebere, Rodgers; Kabaseke, Clovis; Namara, Esther; Dewitte, Olivier; Kervyn, Matthieu; Jacobs, Liesbet
Abstract: Spatio-temporal inventory of natural hazards is a challenging task especially in rural or remote areas in the Global South where data collection at regional scale is difficult. Citizen science, i.e. involvement of no-experts in collecting information and co-creation of knowledge with experts to solve societal and environmental problems, has been suggested as a viable approach to tackle this bottleneck, although the reliability of the resulting data is often questioned. Here we analyse an inventory of geo-hydrological hazards (landslides and floods) reported by a network of citizen scientists in the Rwenzori Mountains, Uganda, established since 2017. We assess the precision, sensitivity and potential biases affecting this citizen science-based hazard inventory. We compare the citizen science-based records with two independent inventories, one collected through systematic fieldwork and another by PlanetScope satellite imagery mapping for the period between May 2019 and May 2020. The precision of the geo-observer data is higher (99% and 100% for landslides and floods, respectively) than that of satellite-based data (44% and 84%, respectively) indicative of fewer false positives in the former inventory. Also, citizen scientists have a higher sensitivity in reporting landslides (51%) compared to satellite imagery (39%) in addition to being able to report the events a few days after the occurrence. In contrast, the sensitivity of satellite-based flood detection is higher than that of citizen scientists. The probability of landslide events being reported by citizen scientists depends both on citizen scientists and hazard specific features (impact, landslide-citizen scientist home distance, landslide-road access distance and altitude). Although satellite imagery mapping could result in a spatially less biased inventory, small landslides are often missed while shallow ones can easily be confused with freshly cleared vegetation. Also, in a dominantly cloudy environment, it can take several days to weeks before a cloud-free satellite image can be obtained. In summary, the typically rapid response time of citizen scientists can result in faster information with high reliability at the risk of missing out almost half of the occurrences. Citizen scientists also provide more data on impact and type of land use, something difficult to achieve using satellite imagery. Working with farmers at village level as citizen scientists can facilitate covering a wider geographical area while reducing the area monitored by each citizen scientist at the same time.